Gambaran Quantitative Electroencephalography (QEEG) Anak Laki-laki Penderita Attention-Deficit Disorder (ADD) - Gea Pandhita S; Sri Sutarni (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2021)
Background. The Diagnostic and Statistical Manual of Mental Disorders (DSM) grouping the types of ADD is based on the clinical symptoms of neurobehavioral disorders, regardless of the possible underlying etiology. This means that the same ADD type group may have a different etiology of functional brain disorders. Meanwhile, QEEG has been known to describe the possible etiology that underlies an ADD event. This study aims to identify differences in QEEG features in the same ADD type group. Methods. Subjects consisted of 40 boys with ADD. QEEG was recorded from 21 sites, and Fourier transformed to provide estimates for relative power in the delta, theta, alpha, and beta bands in the frontotemporal and central regions. These data were converted to Z-scores based on the normal value data; afterward, they were subjected to cluster analysis. Independent sample t-tests were used to determine how the total ADD group and the ADD cluster subgroups differed from the normal value. Results. The total ADD group had increased relative delta (Z-score-frontotemporal region = 3,26 ± 1,59; Z-score-central region = 4,04 ± 1,71), decreased relative alpha (Z-score-frontotemporal region = -2,78 ± 1,29; Z-score-central region = -2,86 ± 1,36), decreased relative beta (Z-score-frontotemporal region = -5,33 ± 1,61; Z-score-central region = -6,19 ± 1,86), increased rasio teta/alpha (Z-score-frontotemporal region = 2,806 ± 1,41; Z-score-central region = 2,59 ± 1,26), and increased rasio teta/beta (Z-score-frontotemporal region = 4,36 ± 1,69; Z-score-central region = 4,94 ± 1,46). Two distinct QEEG clusters subgroups were found. The first cluster was characterized by increased central relative delta (Z-score-central region = 3,02 ± 1,17), decreased relative beta (Z-score-frontotemporal region = -4,29 ± 0,73; Z-score-central region = -5,06 ± 1,19) and increased rasio teta/beta (Z-score-frontotemporal region = 3,83 ± 1,91; Z-score-central region = 4,94 ± 1,96). The second cluster was characterized by increased relative delta (Z-score-frontotemporal region = 4,71 ± 1,02; Z-score-central region = 5,72 ± 0,98), decreased relative alpha (Z-score-frontotemporal region = -3,92 ± 1,12; Z-score-central region = -4,24 ± 0,69), decreased relative beta (Z-score-frontotemporal region = -7,08 ± 1,06; Z-score-central region = -8,09 ± 0,99), increased rasio teta/alpha (Z-score-frontotemporal region = 3,08 ± 1,04; Z-score-central region = 2,86 ± 1,02), and increased rasio teta/beta (Z-score-frontotemporal region = 5,23 ± 1,16; Z-score-central region = 5,71 ± 1,35) Conclusions. These results indicate that boys with ADD do not constitute a homogenous group in QEEG profile terms. Two distinct QEEG clusters were found. The first cluster was typified by a cortically hypoaroused, while the second cluster was typified by a maturational-lag in central nervous system development. This difference in possible etiology may have implications for studies of the utility of QEEG in the diagnosis of ADD and the differences in therapeutic response between the two groups.